PENGARUH MODEL PEMBELAJARAN STAD BERBANTUAN MEDIA PLOTAGON TERHADAP KEAKTIFAN DAN HASIL BELAJAR IPA SISWA KELAS V SD - Leny Wafiyatul Insiyah; Diki Rukmana (PIONIR: JURNAL PENDIDIKAN, 2022)
The learning process at SDN Cibuntu 01 which has not used learning models and interactive media makes learning monotonous and conventional. The purpose of this study was to determine the effect of the Student Teams Achievement Division (STAD) learning model assisted by plotagon media on the activeness and learning outcomes of science in fifth grade elementary school students. This study uses a quantitative experimental approach with the Pre-Experiment method and the One Group Pretest Posttest design. By using saturated sampling technique, the research sample was obtained from one research class consisting of 27 students. The instrument in this study was a learning activity observation sheet and a test of learning outcomes in the form of multiple choice. Based on the results of the analysis of student activity, it was found that tcount (12,913) > ttable (2,064), as well as the results of the analysis of the learning outcomes test obtained tcount (14,736) > ttable (2,064). Based on the results of the analysis, it can be concluded that there is an effect of using the STAD learning model assisted by plotagon media on the activity and learning outcomes of the fifth grade students of SDN Cibuntu 01.